2003
DOI: 10.14507/epaa.v11n36.2003
|View full text |Cite
|
Sign up to set email alerts
|

English Learners in California Schools: Unequal resources, 'Unequal outcomes

Abstract: The Williams vs the State of California class action suit on behalf of poor children in that state argues that California provides a fundamentally inequitable education to students based on wealth and language status. This article, an earlier version of which was prepared as background to that case, reviews the conditions of schooling for English learners in the state with the largest population of such students, totaling nearly 1.6 million in 2003, and comprising about 40 percent of nation’s English learners.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
247
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(262 citation statements)
references
References 52 publications
5
247
0
5
Order By: Relevance
“…Drawing on data from a variety of sources (Gándara, et al, 2003;Rumberger & Gándara, 2004) identified seven inequitable conditions that affect these students' opportunities to learn in California, and which are linked to resources:…”
Section: Conditions For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on data from a variety of sources (Gándara, et al, 2003;Rumberger & Gándara, 2004) identified seven inequitable conditions that affect these students' opportunities to learn in California, and which are linked to resources:…”
Section: Conditions For Learningmentioning
confidence: 99%
“…Moreover, about one third of respondents complained that sessions were of low quality and limited utility. California with large numbers of EL students have fewer adult assistants in them to help provide individual attention for students--an average of 7 hours assistance weekly for classrooms with more than 50% EL students versus 11 hours for those with no ELs (Gándara et al, 2003). California teachers found that among classrooms with over 30 percent EL students, 29 percent of teachers reported not having adequate materials in English for their students, while only 19 percent of teachers with fewer than 30 percent EL students reported this same shortage (cited in Gándara et al, 2003).…”
mentioning
confidence: 99%
“…Structural inequities in the education of minority-language students have been well documented (Gándara, Rumberger, Maxwell-Jolly, & Callahan, 2003;Gutiérrez, 2005). Teachers of ELL students have higher mobility rates (Katz, 1999), schools that serve large numbers of ELL students have poorer infrastructures (Gándara et al, 2003), and ELL students are disproportionately represented in nonacademic or lowtrack classes (Gándara et al, 2003;Harklau, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Teachers of ELL students have higher mobility rates (Katz, 1999), schools that serve large numbers of ELL students have poorer infrastructures (Gándara et al, 2003), and ELL students are disproportionately represented in nonacademic or lowtrack classes (Gándara et al, 2003;Harklau, 1994). Much less is understood, however, Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Specific knowledge and applications of English language, linguistics, language acquisition and cultural implications need to be stressed in the professional development for teachers working with ESL students (August & Hakuta, 1997;Olsen, 2000;Fillmore & Snow, 2002;Gandara et al, 2003;Freeman, 2004). Challenging the assumption that the professional development efforts addressing general multicultural education issues can be easily extended to preparing teachers for ESL students, de Jong and Harper (2005) highlighted the gap between 'just good teaching' and effective ESL instruction.…”
Section: Professional Development Design -Content Focus Coherence Anmentioning
confidence: 99%